8-Isoprostane in chronic periodontitis and type II diabetes: Exploring the link - Arati C Koregol; Nagaraj B Kalburgi; Sireesha Kanniappa Sadasivan; Shivaraj Warad; Apoorva Kamat Wagh; Tivin Thomas; Priya Sinha (Tabriz University of Medical Sciences, 2018)
Background. Reactive oxygen species (ROS) are associated with the pathogenesis of inflammatory diseases and have a direct or indirect role in tissue damage constituting oxidative stress. ROS are also involved in impairment of β-cell function during development of diabetes, which leads to genetic ablation of KATP channels, triggering up-regulation of antioxidant enzymes. Several markers of lipid peroxidation, protein oxidation and DNA damage induced by ROS can be measured. Over the last decade, isoprostanes have been considered as the best markers of lipid peroxidation. The aim of this study was to determine the presence of 8-isoprostane in healthy, chronic periodontitis and chronic periodontitis subjects with type II diabetes and to find the correlation between 8-isoprostane levels among groups and with clinical parameters like gingival index, probing depth and clinical attachment levels. Methods. Ninety subjects were selected and divided into 3 groups: healthy, chronic periodontitis and chronic periodontitis subjects with type II diabetes (n=30 each). Saliva was collected from these subjects after obtaining consent and analyzed for 8-isoprostane levels using ELISA kit. Statistical analysis was performed using Kruskal-Wallis test, Mann-Whitney U test and Spearman's correlation coefficient (P<0.001). Results. Statistically significant difference was found in the levels of 8-isoprostane between healthy, chronic periodontitis and chronic periodontitis subjects with type II diabetes and with all clinical parameters. Conclusion. 8-isoprostane can be considered as a pathophysiological marker to measure oxidative stress in periodontal diseases.